استخدام المعجم"المفردات اليومية" لقسم اللغة بمعهد الروضة الحسنة في ترقية المهارة العربية لدى طلاب الصف الثامن بمدرسة آل عمران الإعدادية الإسلامية ميدان - Juanda, Muhammad Ilham; Haq, Samsul (YASIN, 2025)
Using a pocket dictionary as an Arabic teaching tool to improve Arabic speaking skills. This study aims to obtain descriptive information about the use of pocket dictionaries of daily vocabulary in learning Arabic in MTs ali imron and to find out its advantages and disadvantages. The method used in this study is qualitative descriptive, data is collected starting from the stages of preparation, application, observation, interviews, documentation, and data analysis according to Miles and Hoberman's theory, namely the preparation of data reduction, data presentation and conclusion drawn. The result of the study is the use of a daily vocabulary dictionary used in learning Arabic for eighth grade MTs ali imron, which has advantages and disadvantages in its use. The use of the daily vocabulary dictionary has proven to be effective in improving Arabic language proficiency for eighth graders at Imron, which makes it easier for students to pronounce vocabulary more easily and efficiently and students are able to speak more in speaking proficiency and is designed with initial preparation, material input, vocabulary pronunciation, words with simple sentences, reading, writing and assessment before learning Arabic.